Sustainable distribution practices and environmental performance among chemical firms in Malaysia - Omar, Salmah; Othman, Norfaridatul Akmaliah; Hami, Norsiah; Mustafar, Mastora (School of Technology Management and Logistics (STML), 2019)
The increasing influence of logistics and distribution services in moving Malaysia’s economy which is derived by the globalizations and changing of world trade had dramatically created impact on environment. Legislation has been effective in improving environmental conditions, but emission of pollutants to atmosphere are still discharged in considerable amounts (3.4 billion tons) in 2017 in Malaysia alone (DOSM, 2017). The largest contribution to this pollutants (70.4%) was from car and vehicle (logistics & distribution). Chemical firms have started to green their operations in order to help their customers to be better prepared for predictable and future green demand from both market and government legislation's. Chemical firms in Malaysia is also one of the most developed chemical industries of the world. The industry is not only capable of fulfilling the nation's requirement of chemical products but also exports its chemical products to the countries like Japan, Hong Kong, China, Singapore, Thailand and even U.S.A. The areas in which the chemical industry in Malaysia is specially advanced are the Petrochemicals and Oleo Chemicals (Omar & Othman, 2016).